- #1

- 80

- 0

## Main Question or Discussion Point

I hope someone can help me with this:

Let the the inverse [tex]A A^{-1}=A^{-1} A=I[/tex], where I is the identity operator. Proofing that [tex](AB)^{-1}=B^{-1} A^{-1}[/tex] :

"First, you want to check whether [tex](AB)(B^{-1} A^{-1})=I[/tex]. "

However that means the inverse of AB multiplied by AB gives the identity operator, which isn't true, surely, due to Cramer's rule?

Let the the inverse [tex]A A^{-1}=A^{-1} A=I[/tex], where I is the identity operator. Proofing that [tex](AB)^{-1}=B^{-1} A^{-1}[/tex] :

"First, you want to check whether [tex](AB)(B^{-1} A^{-1})=I[/tex]. "

However that means the inverse of AB multiplied by AB gives the identity operator, which isn't true, surely, due to Cramer's rule?